The impact of Basel I capital requirements on bank behaviour and the efficacy of monetary policy - Juliusz Jablecki (International Journal of Economic Sciences and Applied Research, 2009)
The paper attempts to investigate the influence of the 1988 Basel Accord on bank behavior and monetary policy. It is argued that the Accord was successful in that it forced commercial banks in all of G-10 countries to maintain higher capital ratios. Tentative research suggests, however, that - at least among American banks - the Accord also encouraged the widespread resort to regulatory capital arbitrage techniques, in particular securitization. The paper also reviews the literature on the transmission mechanism of monetary policy and shows that the Basel Accord has affected the bank lending channel.
Keywords: E51; G28; 330; Basel accord; capital ratios; bank regulation; monetary policy